2005
DOI: 10.1002/jcb.20725
|View full text |Cite
|
Sign up to set email alerts
|

Positive correlation between the expression of X‐chromosome RBM genes (RBMX, RBM3, RBM10) and the proapoptotic Bax gene in human breast cancer

Abstract: In a recent report, it has been postulated that the ubiquitous RBM proteins might constitute a novel family of apoptosis modulators. We measured the expression of the X-chromosome RBM genes (RBMX, RBM3, and RBM10) in 122 breast cancers by means of differential RT-PCR. Using the same method, we also studied the expression of the apoptosis-related genes Bcl-2 and Bax. Markers of hormone dependence (estrogen and progesterone receptors), proliferation (Ki67 and DNA-ploidy), angiogenesis (VEGF and CD105), as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 13 publications
5
65
2
Order By: Relevance
“…27 RBPs have also been described as a novel family of apoptosis modulators, 1 and a correlation between the X chromosomerelated RBM genes (RBMX, RBM3 and RBM10) and the pro-apoptotic Bax gene has been shown in breast cancer. 5 Our data add to these findings by the observation that increased RBM3 expression was associated with favorable clinicopathological variables and an improved prognosis in two independent breast cancer cohorts.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…27 RBPs have also been described as a novel family of apoptosis modulators, 1 and a correlation between the X chromosomerelated RBM genes (RBMX, RBM3 and RBM10) and the pro-apoptotic Bax gene has been shown in breast cancer. 5 Our data add to these findings by the observation that increased RBM3 expression was associated with favorable clinicopathological variables and an improved prognosis in two independent breast cancer cohorts.…”
Section: Discussionsupporting
confidence: 67%
“…3 The RBM3 protein binds to both DNA and RNA. 4 Although RBM proteins have been proposed to be a novel family of apoptosis regulators, 1,[5][6][7] the exact function of RBM3 has yet to be fully elucidated. RBM3 transcripts have been found in various human tissues, 3 and in vitro, RBM3 is one of the earliest proteins synthesized in response to mild hypothermia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study has only confirmed the involvement of some genes in cancer; others were left to be further studied. To date, there are a small number of studies reporting RBM10-regulated genes, such as Bax, 12 VEGF, 10 EGFR, 15 FAX, 31 TNF, 22 NUMB, 19 or Fas and Bcl-x genes. 5 Nevertheless, this study does have some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…4 RBM10 can be alternatively spliced to produce RBM10 RNA variant 1 and variant 2, which encode nuclear RNA-binding proteins containing zinc finger motifs, a G-patch, and two RNA Recognition Motif (RRMs) to regulate gene transcription, mRNA alternative splicing, and stabilization of various genes, including apoptosis-related Fas and Bcl-x genes. 5 RBM10 is widely expressed in a variety of cells and tissues, 6,7 and altered RBM10 expression has been reported in TARP syndrome (talipes equinovarus, atrial septal defect, Robin sequence, and persistent left superior vena cava syndrome), X-linked disorder, 8,9 and various human cancers, such as breast cancer, [10][11][12] pancreatic cancer, 13 and metastatic melanoma. 14 In lung cancer, a comprehensive molecular profiling study of lung adenocarcinoma demonstrated that mutations of epidermal growth factor receptor (EGFR) were more frequent in females, whereas mutations in RBM10 were more common in male patients.…”
Section: Introductionmentioning
confidence: 99%